2006
DOI: 10.1002/bem.20221
|View full text |Cite
|
Sign up to set email alerts
|

The influence of continuous exposure to 50 Hz electric field on nerve regeneration in a rat peroneal nerve crush injury model

Abstract: The effect of power frequency electric field (EF) on nerve regeneration was investigated on a rat peroneal nerve crush injury model. The animals were assigned to three groups: 50 Hz EF and Static EF groups were exposed at 10 kV/m. The sham group was kept in the same setting without any EF applications. EF was uninterruptedly applied for 21 days postoperatively. Repeated measures analysis of daily walking tracks during EF exposure demonstrated lower toe spread recovery (TSR) in the 50 Hz EF group. Significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Thus, low ATP concentrations may have led to impairment of the normal regeneration process. Aydin et al (2006) submitted rats with a peroneal crush lesion to a whole‐body exposure of a 50‐Hz biphasic electrical field with an estimated induced electrical field of 10 mV/m and found a weak inhibition of regeneration expressed by morphological defects that did not interfere with gait function. It is difficult to estimate the strength of the electrical field when using the mouse model because the dielectric constant of mice is not yet known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, low ATP concentrations may have led to impairment of the normal regeneration process. Aydin et al (2006) submitted rats with a peroneal crush lesion to a whole‐body exposure of a 50‐Hz biphasic electrical field with an estimated induced electrical field of 10 mV/m and found a weak inhibition of regeneration expressed by morphological defects that did not interfere with gait function. It is difficult to estimate the strength of the electrical field when using the mouse model because the dielectric constant of mice is not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to estimate the strength of the electrical field when using the mouse model because the dielectric constant of mice is not yet known. However, considering that a field magnitude of 10 mV/m would be the minimal induced field necessary to overcome the basic endogenous noise in cellular membranes and produce physical and biological effects ( Astumian et al, 1995; Aydin et al, 2006 ) , even very low electrical field intensities could cause negative biological effects on regeneration. Chen et al (2001) also found adverse detrimental consequences of electrical fields on peripheral nerve regeneration using percutaneous electrodes and a 1‐mA monophasic current.…”
Section: Discussionmentioning
confidence: 99%
“…Since the conductivity of water is very low at this operation frequency, water in all the living tissues and water bottles would be ineffective on the field lines produced in an exposed environment (Aydin et al, 2006; Okudan et al, 2006). As a precaution to avoid the slightest unwanted changes in the electrical properties, the cages were maintained clean.…”
Section: Methodsmentioning
confidence: 99%
“…They were placed upright on wooden stands and positioned parallel to each other. In order not to disturb the field, leads were connected to the center of the plates on their outer sides (Aydin et al, 2006;Okudan et al, 2006).…”
Section: Electric Field Application Set-upmentioning
confidence: 99%